Branje delte Biserne reke s stališča Alda Rossija - Pipan, Tomaž (Urbani izziv, 2008)
This article confronts the Rossi's methodology of reading the city with Shenzhen - Chinese contemporary city that developed from a village into a city of 4 million inhabitants in less than 15 years. The article identifies the core instruments of Rossi's theory as presented in his book Architecture of the City and systematically redeploys and tests them on the city in question. Through this a critical evaluation of the methodology is made, furthermore possible modifications are suggested.
Keywords: Biserna reka; Kitajska; Rossi, Aldo; Šenzen; urbanism; urbanistični razvoj; urbanizem